Pectoralis major ruptures during rugby league tackling — Case series with implications for tackling technique instruction - Sartori, S.; Whiteley, R. (Journal of Science and Medicine in Sport, 2019)
Objectives: Document the mechanism and incidence of pectoralis major ruptures in a professional rugby league cohort, and compare to any existing data. Design: Retrospective case series. Methods: Case series which documents 3 such injuries incurred while effecting a tackle in 3 rugby league players from the same squad (of 36) in the same season. Results: At the initial point of contact, all three players were in a similar shoulder position of outer-range abduction and horizontal abduction and subsequently it appeared their pectoralis major was torn while attempting to effect the tackle. Conclusions: Complete tears of the pectoralis major muscle are rare but significant injuries often requiring surgical intervention to restore full function in collision sport athletes. In this same season, the organisation changed their defensive approach which may have contributed to these injuries. Each player was managed with acute surgical repair and returned to play at the same level. Suggestions are made to consider the possible training injury implications of changing tackle technique.